Non-Invasive Ventilation in a Non-Standard Setting – Is it Safe to Ventilate Outside the ICU? - Boyadzhieva I. (Sciendo, 2020)
Non-invasive ventilation (NIV) is considered a fundamental method in treating patients with various disorders, requiring respiratory support. Often the lack of beds in the intensive care unit (ICU) and the concomitant medical conditions, which refer patients as unsuitable for aggressive treatment in the ICU, highlight the need of NIV application in general non-monitored wards and unusual settings – most commonly emergency departments, high-dependency units, pulmonary wards, and even ambulances. Recent studies suggest faster improvement of all physiological variables, reduced intubation rates, postoperative pulmonary complications and hospital mortality with better outcome and quality of life by early well-monitored ward-based NIV compared to standard medical therapy in patients with exacerbation of a chronic obstructive pulmonary disease, after a surgical procedure or acute hypoxemic respiratory failure in hematologic malignancies. NIV is a ceiling of treatment and a comfort measure in many patients with do-not-intubate orders due to terminal illnesses. NIV is beneficial only by proper administration with appropriate monitoring and screening for early NIV failure. Successful NIV application in a ward requires a well-equipped area and adequately trained multidisciplinary team. It could be initiated not only by attending physicians, respiratory technicians, and nurses but also by medical emergency teams. Ward-based NIV is supposed to be more cost-effective than NIV in the ICU, but further investigation is required to establish the safety and efficacy in hospital wards with a low nurse to patient ratio.